2015
DOI: 10.1107/s2052252515012221
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of thin film pair distribution function analysis (tfPDF) for the study of local structure in amorphous and crystalline thin films

Abstract: It is shown how normal-incidence X-ray total scattering can be used to obtain high-quality pair distribution functions from amorphous and crystalline thin films on much thicker substrates, allowing a range of studies of the local structure in film materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…It is clear that other methods are needed for a complete understanding of the structure of nanoparticles.High-energy XRD (HE-XRD) measurements combined with a Pair Distribution Function (PDF) analysis can yield valuable information on the short-range atomic ordering of nanocrystalline materials with some degree of structural coherence and periodicity. A large body of literature [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] details how the PDF analysis can enable a complete structural investigation of a nanostructured material. Application to nanomaterials, however, has become practical only recently, with the advent of high-flux and high-energy synchrotron radiation sources.…”
mentioning
confidence: 99%
“…It is clear that other methods are needed for a complete understanding of the structure of nanoparticles.High-energy XRD (HE-XRD) measurements combined with a Pair Distribution Function (PDF) analysis can yield valuable information on the short-range atomic ordering of nanocrystalline materials with some degree of structural coherence and periodicity. A large body of literature [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] details how the PDF analysis can enable a complete structural investigation of a nanostructured material. Application to nanomaterials, however, has become practical only recently, with the advent of high-flux and high-energy synchrotron radiation sources.…”
mentioning
confidence: 99%
“…However, both electron PDF, and PDF from delaminated films are destructive measurements. Recently, there was a report of a non-destructive tour-the-force measurement by Jensen and co-workers20 in which they isolate the total scattering of a 360 nm film grown on a relatively thin (170 microns) borosilicate glass by careful subtraction of the substrate contribution. Obtaining total scattering from a thin film via carefully subtraction of scattering from the substrate, despite being non-destructive, has some inherent limitations.…”
mentioning
confidence: 99%
“…This experimental design promotes localized crystallization and growth of TiO 2 films on the conducting layer. Utilizing thin film PDF data acquisition and analysis methods 36 at the National Synchrotron Light Source II (NSLS-II) at Brookhaven National Laboratory, it was found that TiO 2 films grown by MWR-assisted synthesis at a solution temperature of 160°C contained long-range crystalline anatase phase TiO 2 mixed with a locally ordered amorphous component. PDF fitting revealed that this amorphous component could be estimated by a 77:23 brookite:anatase ratio.…”
Section: Ex Situ Synchrotron X-ray Studies Of Mwr-assisted Synthmentioning
confidence: 99%